Rheumatoid Vasculitis as a Complication of Rheumatoid Arthritis: Two Case Reports - Liñán Ponce, Freddy Octavio (2025)
Rheumatoid vasculitis is a rare, poor-prognosis complication of rheumatoid arthritis, occurring in less than 1% of cases. It presents as digital vasculitis, leukocytoclastic vasculitis, or medium/small-vessel vasculitis. Scott and Bacon’s criteria are used for classification. This report describes two cases with unusual presentations, their diagnostic approach, and treatment. Both presented with lower limb ulcers, general malaise, and elevated rheumatoid factor. Histopathology confirmed small-vessel vasculitis. Both were treated with methotrexate and prednisone with favorable outcomes. The report highlights the importance of considering rheumatoid vasculitis in the differential diagnosis of non-healing ulcers.